Maritime School Gets Budget Hike - Baldwin, John F. (Vallejo Times-Herald)
The budget which was submitted to Congress recently by President Eisenhower contained good news as far as the California Maritime Academy at Vallejo is concerned. The Budget recommended an appropriation of $1,100,000 for the four State Maritime Academies(these are located in California, Maine, Massachusetts, New York). This is almost double the appropriation of $660,000 made 1ast year. The reason for this increase is a law enacted by Congress last year.